The benefits of regional infrastructure investment in Asia: A quantitative exploration - Fan Zhai (Asian Development Bank Institute (ADBI), 2010)
Capitalizing on recent estimates of infrastructure financing requirements in Asia, this paper frames a scenario for infrastructure development in the region and estimates the external effects of infrastructure investment. It also assesses quantitatively the economy-wide welfare effects of developing regional infrastructure in Asia, using a global computable general equilibrium model. The results show that developing Asian economies would gain significantly from the expansion of regional infrastructure in transport and communication. With annual investment of around US800 billion in transport, communication, and energy infrastructure during 2010-2020, developing Asia is likely to reap welfare gains of US1,616.3 billion (in 2008 prices) in 2020, or 10% of projected aggregate gross domestic product.
Keywords: C68; F15; 330; Infrastrukturinvestition; Externer Effekt; Wohlfahrtseffekt; Asien